Inclusive Education: Dismal Future - Somaiah , Malathi (INDIAN EDUCATIONAL REVIEW, 2009)
There has been enormous thrust in the National Policy on Education, 1986 to mainstream disabled children in the Elementary Education programme. The current survey by NUEPA provides valuable data on the status of integrating disabled children under inclusive Education. This paper looks at the paradigm shift in the education of the disabled, focus on International Scenario; highlight the disparities across states in India. Finally, the paper examines the implication of Data for strengthening Inclusive Education. The paper concludes with the emphasis that the Government should work towards providing high quality Education to the disabled and provide relevant training to teachers. This should be an integral part of the implementation of Sarva Shiksha Abhiyan. The dream of Universalisation Elementary Education will be fulfilled after every disabled child is integrated into the mainstream of Education.